A Security Home System Feature as a Part of Home Assistant through IoT Platform - Yasri, Indra; Al-Alif, Ahmad; Pirwanhadi, Faril (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2025)
The rapid development of Internet of Things (IoT) revolutionized the method to secure and monitor our homes. As smart home technology becomes increasingly accessible, the integration of robust, scalable, and cost-effective security systems is no longer a luxury but a necessity. This study proposed the creation and development of a home security system integrated with Home Assistant and Tailscale VPN using the ESP32-CAM WROVER microcontroller. By leveraging the IoT ecosystem, the system features real-time door detection, intrusion alarms, and remote monitoring capabilities. A reed switch sensor detects door or window activity, while the ESP32-CAM WROVER captures and transmits images of potential intrusions to a Linux-based Hass.io server. Notifications and images are sent to the user’s smartphone for real-time updates, ensuring timely responses to security threats. The system is secured via a Tailscale VPN, allowing authorized users seamless access through MagicDNS. The research highlights the cost-effectiveness and efficiency of utilizing Linux-based virtual machines for smart home applications, as well as the performance advantages of the ESP32-CAM WROVER microcontroller. System testing performed by a single user with several activation attempts shows a success rate of 93.33% for the alarm output, with a 6.67% error rate attributed to rapid state changes or hardware noise. In contrast, the camera snapshot component demonstrated 100% reliability, with no errors in capturing or transmitting images. Comprehensive tests confirm the system’s ability to enhance home security with its scalable and flexible architecture, making it a practical solution for modern smart homes.